Assessment of a Modified DSM‐5 Diagnosis of Alcohol Use Disorder in a Genetically Informative Population. (24th January 2013) - Edwards, Alexis C.; Gillespie, Nathan A.; Aggen, Steven H.; Kendler, Kenneth S.
<x xml:space="preserve">Abstract</x> Background Proposed changes to the upcoming DSM‐5 include the following: (i) combining criteria for DSM‐IV alcohol abuse (AA) and alcohol dependence (AD) into 1 diagnostic category (alcohol use disorder [AUD]); (ii) exclusion of the "legal problems" (LP) criterion; and (iii) addition of a "craving" criterion. Few published studies empirically assess the potential consequences of the proposed changes. Methods Using a population‐based sample of twins assessed for lifetime AA/AD diagnoses, we explored phenotypic differences across DSM‐IV and a modified DSM‐5 diagnoses without craving because of its unavailability in the data set. We used factor analysis and item response theory (IRT) to evaluate the potential consequences of excluding the LP criterion from AUD and used twin modeling to examine genetic differences between DSM‐IV and the modified DSM‐5 diagnoses. Results The prevalence of AUD was slightly higher than that of DSM‐IV diagnoses. Individuals meeting DSM‐IV or DSM‐5 criteria, but not both, exhibit fewer comorbid diagnoses than those meeting both sets of criteria. Individuals meeting only DSM‐5 criteria were slightly less severely affected than those meeting only DSM‐IV criteria. Factor analysis indicated that the LP criterion loading is the lowest of all symptoms; IRT analysis suggested that this criterion has low discriminatory power. The genetic correlation between DSM‐IV and DSM‐5 diagnoses was slightly but significantly lower than unity. Conclusions The proposed DSM‐5 AUD criteria are unlikely to result in significant changes in prevalence of diagnosed alcohol problems. However, it is unclear whether the new criteria represent a more valid diagnosis: new cases are no more severely affected than DSM‐IV‐only cases. Given the psychometric properties of LP, its exclusion should not negatively impact diagnostic validity. Similarly, the stable heritability across DSM‐IV and DSM‐5 diagnoses suggests that the proposed changes will not have substantial negative consequences in terms of familial influences, a key validator. These results provide equivocal empirical support for the proposed DSM‐5 changes for AUDs.